FACTORS INFLUENCING THE PURCHASE INTENTION OF HALAL PACKAGED FOOD IN THAILAND - Syukur, Muhammad; Nimsai, Suthep (International Journal of Supply Chain Management, 2018)
Halal market has been expanding staggeringly. It has a great potential to grow the global economy. Muslim minority countries like Thailand start to see the opportunity and penetrate the halal food market to boost the local economy. However, there is still a knowledge gap considering the importance of studying the halal market and the limited availability of academic resources. This research will contribute to being a reference of halal study in the future for examining the consumers purchase behavior of halal food. Due to that, this paper aims to investigate the factors that can influence purchase intention of halal food among the Muslim consumers in Thailand. The data were collected from 480 respondents. The purposive sampling method is used to gather respondents from the four regions: the northern, the central including Bangkok, the northeastern, and the southern part of Thailand. Multiple linear regression analysis reveals that product characteristics, places to display the products in retailing shops, halal awareness from the consumers, and the religiosity level are significantly influencing the consumers purchase intention of halal food in Thailand. The price of the product, promotion, and the consumers knowledge about halal food supply chain cannot influence the purchase intention of halal food.